Menurunkan CVD (Cardio Vaskuler Disease) Risk Karyawan PT Putra Perkasa Abadi Site PT Makmur Lestari Primatama Sebesar 50% dengan Program Heart Health Heroes - Ashthofi Zainati; Fikri Fahmi A; Akhmad Maulana Ibrahim (Journal of Applied Agriculture, Health, and Technology, 2024)
Cardiovascular Disease (CVD) is the leading cause of death worldwide, including in Indonesia. According to WHO, CVD accounts for an estimated 17.9 million deaths annually. In the Western Pacific region, CVD contributes to 40% of deaths, approximately 5.7 million cases. This trend is projected to rise by 91.2% between 2025 and 2050. In Indonesia, the prevalence of CVD reached 0.85%, or approximately 877,531 cases, in 2023. PT Putra Perkasa Abadi (PPA) Site MLP faces similar challenges with an increasing risk of CVD among its employees. Between 2022 and 2023, two cases of CVDrelated fatalities occurred in the workplace, and data showed a 30% increase in employees at risk of CVD compared to the previous year. The highest risk factors include active smoking (45%), BMI >30 (14%), high cholesterol (13%), elevated triglycerides (11%), hypertension (4%), and diabetes (2%). This study aims to reduce the risk of CVD among employees by 50% through the implementation of the Heart Health Heroes Program. The program's targets include a 100% reduction in high- and mediumrisk categories and a 50% reduction in the low-risk category, with the ultimate goal of achieving zero cases of CVD-related fatalities by 2024. Additionally, the program seeks to improve employee health levels by reducing the Crude Mortality Rate (CMR) and Absence Severity Rate (ASR). The research utilizes an Experimental Factorial Design method with a quantitative approach. Data were collected from the employees' Medical Check-Up (MCU) records for 2022 and 2023. CVD risk was categorized using the Framingham Risk Score (FRS) into three categories: low risk (FRS <10%), medium risk (FRS 10–19%), and high risk (FRS >20%). The data analysis technique employed is quantitative data analysis. The results showed a significant reduction in cardiovascular disease (CVD) risk across all categories, with the highest reduction observed in the High Risk category, which decreased by 75%. Overall, there was a 40% reduction in CVD risk among all employees at PT Putra Perkasa Abadi Site MLP. Key risk factor reductions included hypertension (71%), diabetes (50%), active smoking (42%), BMI >30 and cholesterol (36%), and triglycerides (29%). These results demonstrate the effectiveness of the program in managing CVD risk factors.